Tanggung Jawab Developer Dalam Pembuatan Akta Jual Beli Atas Rumah Yang Telah Lunas Dibayar - Fadli Adi Rosadi; Tofik Yanuar Chandra; Anriz Nazaruddin Halim (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The need for housing is increasing rapidly, especially in urban communities due to the large population. This is put to good use by developers who are entrepreneurs in the housing sector, to take maximum advantage. Even though consumer rights have been clearly regulated in the UUPK and of course, consumers and business actors will rely on these transactions based on sale and purchase agreements that occur between consumers/buyers and business actors (developers/housing developers) and one of the elements contained in the agreement is good faith. The type of research used in this study is normative legal research or also known as research for the purposes of legal practice. For ordinary people, the type of house sale and purchase agreement can be complicated and intimidating. Even though they contain very important things that you as a homeowner should know.